OPTIMALISASI NILAI PEMANFAATAN WAKAF DARI FUNGSI SOSIAL MENJADI EKONOMIS DI KOTA SEMARANG - Joko Dwi Widiyanto; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The purpose and this research is for the existence of function and benefit of waqf as well as factors influencing the existence of function and manfat of waqf, solution and solution about function and benefit of waqf in society after notarial deed and social function become function in town of SemarangThis research is empirical law research, that is research based on the implementation of optimization of social wakaf utilization value into a frugal function in Semarang City The existence of shifting funngsi and wakaf benefits in Semarang City in the formulation of the transfer function by granting the previous waqf. Factors that affect the function and benefits are by way of selling and the results used to purchase new and broad wakaf data obtained are analyzed quantitatively.Optimizing the benefits of the utilization of waqf from social function into a frugal function in the city of Semarang by the researchers, then at the end of the series of research activities of this Thesis, will be concluded about the practice of transferring wakaf by nazhir Pedurungan Sub-district of Semarang that has been found, the existence of shifting funngsi And Benefits of waqf in Semarang City in the way of testing by granting the previous waqf, factors influencing the existence of the functions and benefits by way of selling and the results used to buy a new waqf, the implementation of the transfer function is done by granting the previous waqf After being dismantled As a waqf object that pole mosque, roof and windows, and the floors derived from the wakaf of the mosque maker's waqf objects is no longer functioned as a waqf object of the mosque that comes from ulin wood, all the wakaf objects that dibabak is granted to Other mosques y Ang need.The reason for the constraints on the function and benefits of wakaf in the community after the notarial deed of the social function became the basic economic function of the practice of transferring wakaf function by nazhir in Kecamatan Pedurungan Semarang City is as follows: Because the mosque can not accommodate the number of jama